Federal government budgetary and financial resources for body practices and physical activities in the Unified Health System: analysis of the 2019-2022 governmental cycle - de Carvalho, Fabio Fortunato Brasil; Loch, Mathias Roberto; Sposito, Letícia Aparecida Calderão [UNESP]; Andrade, Douglas Roque; Vieira, Leonardo Araújo (FapUNIFESP (SciELO), 2024)
Through quantitative exploratory re-search, the present study analyzed the amount foreseen in the Federal Budget and the amounts paid (nominal and deflated) for programs and actions to promote body practices and physical activities (Health Academy Program and the Federal Incentive for Physical Activity in Primary Health Care) from 2019 to 2022. The values of investment in body practices and physical activities in SUS per capita, according to the population covered by Primary Health Care (PHC) and per participant in public programs, were also calculated. The following was found: (1) that the resources that were actually paid were 3.31% to 15.06% lower than those approved in the budget (nominal) and (2) the low annual (maximum) values found, regardless of whether nominal or deflated – per capita (R$ 0.21 to 0.30) per population covered by PHC (R$ 0.25 to 0.40) and per participant (R$ 10.61 to 14.61). It was concluded that the low investment in the promotion of body practices and physical activities decreases access and does not contribute to the full functioning of SUS by preventing or hindering the expansion of possibilities of comprehensive health care.
Recursos da União para as práticas corporais e atividades físicas no SUS: análise do ciclo governamental 2019-2022
Keywords: Government funding; Health policy; Health pomotion